2016
DOI: 10.1177/0044118x15575290
|View full text |Cite
|
Sign up to set email alerts
|

Getting In, Being In, Staying In, and Getting Out

Abstract: Dating is a highly desirable experience during adolescence and serves as an important developmental milestone. This study explored healthy and unhealthy dating as a step toward improving adolescent well-being. Six focus group interviews were conducted with high school-aged girls and boys (N = 35). Interviews were audio recorded, transcribed verbatim, and analyzed using a grounded theory approach. Youth were asked to describe what dating was like for teens in their age, including dating problems. Narrative anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 60 publications
(81 reference statements)
2
10
0
2
Order By: Relevance
“…Another form of management reported by the participants of the present study was to activate their support networkrepresented by parents and friends -, police, as well as psychologists to help in coping with situations of violence in their relationships. These same mechanisms of support were also pointed out by other authors, and the friends were the ones most activated by adolescents (22)(23)(24) . It is worth noting that the search for friends is justified, above all, by the characteristics of empathy, warmth, secrecy and posture of non-judgment (25) .…”
Section: Discussionsupporting
confidence: 83%
“…Another form of management reported by the participants of the present study was to activate their support networkrepresented by parents and friends -, police, as well as psychologists to help in coping with situations of violence in their relationships. These same mechanisms of support were also pointed out by other authors, and the friends were the ones most activated by adolescents (22)(23)(24) . It is worth noting that the search for friends is justified, above all, by the characteristics of empathy, warmth, secrecy and posture of non-judgment (25) .…”
Section: Discussionsupporting
confidence: 83%
“…Some respondents described their engagement in controlling and monitoring behaviors out of "curiosity" and "interest in their romantic partner" rather than with the intent to control or monitor. This squares with prior research, which found that adolescents often do not perceive acts of (online) dating violence within their relationships as problematic (Helm et al, 2015;Lucero et al, 2014). Baker and Helm (2010) found, for instance, that teenagers who are victims of controlling and monitoring behaviors mostly regard them as annoying or irritating and do not necessarily describe them as dating violence.…”
Section: Monitoringsupporting
confidence: 77%
“…Baker and Helm (2010) found, for instance, that teenagers who are victims of controlling and monitoring behaviors mostly regard them as annoying or irritating and do not necessarily describe them as dating violence. This may cause them to remain within abusive and unhealthy romantic relationships rather than leaving them (Helm et al, 2015). Our finding further highlights the need for relationship education to focus on healthy relationship skills and to discuss examples of healthy and unhealthy behaviors within romantic relationships.…”
Section: Monitoringmentioning
confidence: 73%
See 1 more Smart Citation
“…The associations between negative interactions and adolescent adjustment can be understood in the context of the stress and coping model (Davila, 2008). Because adolescents have limited experience with romantic relationships, they may interpret negative interactions, even inevitable normative conflict, with their romantic partners as signs they are being rejected or the relationship is ending (La Greca & Harrison, 2005;La Greca & Mackey, 2007), both of which are distressing to adolescents (Helm, Baker, Berlin, & Kimura, 2017). Limited experience with romantic relationships may mean adolescents lack appropriate coping skills for relationship stressors (Davila, 2008), which is positively associated with susceptibility to depressive symptoms and externalizing behavior (Downey, Bonica, & Rincon, 1999;Welsh et al, 2003).…”
Section: Low Positive Interactionsmentioning
confidence: 99%